Ecological Networks between Tent-Roosting Bats (Phyllostomidae: Stenodermatinae) and the Plants Used in a Neotropical Rainforest - Rodríguez Herrera, Bernal (2018)
Roost ecology in bats is a complex interaction of behavioral, morphological and physiological adaptations, thus, there are many factors involved in roost selection by bat species. Approximately 22 species of bats are able to modify leaves to establish their roost, 17 of which are in the Neotropics. Although there are many studies of tent-roosting bats, this is the first describing the structure of the interaction between bats and the plants they are using as roosts. We describe a potential antagonistic network between these bats and the plants used for tent construction in La Selva Biological Station in Costa Rica. We calculated descriptors of the network such as the number of bats and plants interacting, as well as the number of pairwise interactions based on published records or direct observations. We also tested for connectance and nestedness in the network structure. We propose a name for this non-trophic antagonistic interaction, which is a structural antagonism, where bats damage the leaves, reducing their lifespan and the plant fitness. In La Selva the network is composed of eight bats and 45 plant species reported by 60 pairwise interactions. Only 2.16% of vascular plant species in La Selva are being modified as tents. The network had low connectance (0.167) and no significant nestedness or modularity. Considering the species richness of plants in La Selva, there are few links between tent-roosting bats and plants species, which shows the specialization of these interactions and the high dependence of most of these bats on a few plant species, even if they are very specific and temporary resources.